Formation of a multi‐layered 3‐dimensional structure of the heterochromatin compartment during early mammalian development. (3rd February 2021) - Poonperm, Rawin; Hiratani, Ichiro
Abstract: During embryogenesis in mammals, the 3‐dimensional (3D) genome organization changes globally in parallel with transcription changes in a cell‐type specific manner. This involves the progressive formation of heterochromatin, the best example of which is the inactive X chromosome (Xi) in females, originally discovered as a compact 3D structure at the nuclear periphery known as the Barr body. The heterochromatin formation on the autosomes and the Xi is tightly associated with the differentiation state and the developmental potential of cells, making it an ideal readout of the cellular epigenetic state. At a glance, the heterochromatin appears to be uniform. However, recent studies are beginning to reveal a more complex picture, with multiple hierarchical levels co‐existing within the heterochromatin compartment. Such hierarchical levels appear to exist in the heterochromatin compartment on autosomes as well as on the Xi. Here, we review recent progress in our understanding of the 3D genome organization changes during the period of differentiation surrounding pluripotency in vivo and in vitro, with a focus on the heterochromatin compartment. We first look at the whole genome, then focus on the Xi, and discuss their differences and similarities. Finally, we present a unified view of how the heterochromatin compartment is formed and regulated during early development. In particular, we emphasize that there are multiple layers within the heterochromatic compartment on both the autosomes and the Xi, with regulatory mechanisms common and specific to each layer. Abstract : Progressive formation of heterochromatin occurs during early embryogenesis in mammals, affecting the autosomes as well as the inactive X chromosome in females. On the surface, the heterochromatin compartment appears to be uniform. However, recent studies are beginning to reveal a more complex picture, with multiple hierarchical levels co‐existing within the heterochromatin compartment.